Life, Liberty, and the Pursuit of Health - Maddineni, Upendra (Ars Medica, 2016)
Exchange between William Ernest Henley, the 19th century English Poet who wrote Invictus, originally untitled, while in the hospital, and the American Doctor who hears the chorus two centuries later on Independence Day.